IMPLEMENTASI KEGIATAN MAGANG DI BGTK DAN PT SRIWIJAYA DALAM PENINGKATAN KOMPETENSI MAHASISWA - Nayla Maesa Ayu; Nabila, Nanda; Santi A. Ramadhani; Kayla Febhezanisa; Henna; Feni Hercita Saputri; Juaidah Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Merdeka Belajar Kampus Merdeka (MBKM) internship program is designed to provide experiential learning through direct involvement in professional institutions. However, internship activities often emphasize student competence development rather than addressing the concrete needs of partner institutions. This community service activity was implemented at the Teacher and Education Personnel Center of South Sumatra Province and PT Sriwijaya. The main problems identified include administrative inefficiency, limited documentation systems, and suboptimal digital data management. The program aimed to provide structured administrative assistance and digitalization support. The implementation applied a participatory approach with descriptive qualitative techniques. The results showed improved administrative organization, better data verification accuracy, more systematic documentation, and enhanced digital educational content dissemination. These findings indicate that the MBKM internship model can function as a problem-solving community service strategy that strengthens institutional governance while supporting experiential student learning.